STIMULASI PERKEMBANGAN ASPEK SENI ANAK USIA DINI - Istiqomah, Ani Sofiana; Enenti, Dainty Khusna Victoria; Faisal, Vava Imam Agus (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2024)
This study aims to determine the process of stimulating early childhood art development in Banca Patola Kindergarten, Bouban City. The study applies a qualitative descriptive method in which data is collected through observation, interviews, and documentation. The collected data is analyzed by reducing, presenting, and verifying. The results of the study show that the process of stimulating children's artistic development is carried out with activities such as: (1) humming and singing while doing something, (2) creating with beads, origami paper and natural materials; (3) sanis activities such as mixing colors, finger painting; (4) drawing in various ways and forms: (5) coloring activities. In addition, various stimuli that can be applied to improve the achievement of aspects of artistic development at Banca Patola Kindergarten include (1) the role of teachers in providing support and facilities so that children can listen to the songs they like; (2) teachers always give appreciation in the form of praise; (3) teachers facilitate activities that stimulate children's art: (4) teachers give rewards to children for their achievements in activities